Feminist epistemologies - Alcoff, Linda Martín.; Potter, Elizabeth (Thinking gender, 1993)
Il s'agit de la première collection de théoriciennes féministes influentes à se concentrer sur le cœur de l'épistémologie traditionnelle, traitant de questions telles que la nature des connaissances et l'objectivité dans une perspective de genre.
Keywords: approches et analyses; cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; philosophie; point de vue situé; ressource en ligne; sciences humaines; thématiques; épistémologie

What are friends for?: feminist perspectives on personal relationships and moral theory - Friedman, Marilyn (Cornell University Press, 1993)
A contribution to the feminist discussion on moral theory, exploring the debate between moral impartiality and the partiality that characterizes personal relationships, the ethic of care and its relation to justice in a gender asymmetrical society, and the role of intimate friendship in an era of the dissolution of both extended and nuclear families.
Keywords: 1900-1999; 1980-1989; amour; amérique du nord; amériques; approches et analyses; care; cours; discipline; phi2030; philosophie; point de vue situé; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; thématiques; états-unis; éthique